Effect of Massage Therapy for the Treatment of Neonatal Jaundice: A Systematic Review and Dose-Response Meta-analysis - Marjan Shahbazi; Salman Khazaei; Samad Moslehi; Fatemeh Shahbazi (Hindawi Limited, 2022)
Background. The effectiveness of massage therapy in the treatment of neonatal jaundice has been established in previous literature, but how much the level of massage can reduce the mean of bilirubin in neonates with jaundice is a question that has been addressed in this review. Methods. Four electronic databases, including Cochrane, PubMed, Scopus, and Web of Science, were searched for relevant literature. For the dose-response association between massage therapy and treatment of neonatal icterus, we conducted a meta-analysis using the random-effects model. For any level of intervention, we calculated the overall mean difference (MD) with 95% confidence intervals (CI). Results. Twenty studies were included in our meta-analysis. There was a positive and significant increasing dose-response trend between massage therapy and the mean reduction of bilirubin in neonates with hyperbilirubinemia as follows: <50 minutes massage during the experiment -0.36 (95% CI: -0.67, -0.06; I2=66%), 50-60 minutes massage during the experiment -0.41 (95% CI: -0.95, 0.13; I2=84%), and ≥101 minutes massage during the experiment -1.20 (95% CI: -1.63, -0.78; I2=83%). The heterogeneity across studies was mild to moderate. Conclusions. The presence of a dose-response relationship favors the causal relationship between massage therapy and reduction of neonatal jaundice.